Resolving local configurational contributions to X-ray and neutron radial distribution functions within solutions of concentrated electrolytes – a case study of concentrated NaOH. Issue 13 (8th January 2019) - Semrouni, David; Wang, Hsiu-Wen; Clark, Sue B.; Pearce, Carolyn I.; Page, Katharine; Schenter, Gregory; Wesolowski, David J.; Stack, Andrew G.; Clark, Aurora E.
Abstract : Stable local configurations in concentrated electrolytes have distinct X-ray and neutron radial distribution functions that help understand solution structure and speciation. Abstract : Extreme conditions of complex materials often lead to a manifold of local environments that challenge characterization and require new advances at the intersection of modern experimental and theoretical techniques. In this contribution, highly caustic and viscous aqueous NaOD solutions were characterized with a combination of X-ray and neutron radial distribution function (RDF) analyses, molecular dynamics simulations and sub-ensemble analysis. While this system has been the topic of some study, the current work expands upon the state of knowledge regarding the extent to which water is perturbed within this chemically extreme solution. Further, we introduce analyses that goes beyond merely identifying the different local environments (ion solvation and coordination environments) that are present, but toward understanding their relative contributions to the ensemble solution RDF. This integrated approach yields unique insight into the experimental sensitivity of RDFs to changes in local geometries, the composition of solvation environments about ions, and the challenge of experimentally differentiating the ensemble of all superimposed local environments—a feature of increasing importance within the extreme condition of high ionic strength.